How to improve initial diagnostic accuracy of kidney tumours in childhood?: a non-invasive approach - Welter, Nils; Metternich, Gregor; Furtwängler, Rhoikos; Bayoumi, Ahmed; Mergen, Marvin; Kager, Leo; Vokuhl, Christian; Warmann, Steven W.; Fuchs, Jörg; Meier, Clemens-Magnus; Melchior, Patrick; Gessler, Manfred; et al. (International journal of cancer, 2024)
Non-invasive differentiation of paediatric kidney tumours is particularly important in the SIOP-RTSG protocols, which recommend pre-operative chemotherapy without histological confirmation. The identification of clinical and tumour-related parameters may enhance diagnostic accuracy. Age, metastases, and tumour volume (TV) were retrospectively analysed in 3306 patients enrolled in SIOP/GPOH 9, 93-01, and 2001 including Wilms tumour (WT), congenital mesoblastic nephroma (CMN), clear cell sarcoma (CCSK), malignant rhabdoid tumour of the kidney (MRTK), and renal cell carcinoma (RCC). WT was diagnosed in 2927 (88.5%) patients followed by CMN 138 (4.2%), CCSK 126 (3.8%), MRTK 58 (1.8%) and RCC 57 (1.7%). CMN, the most common localized tumour (71.6%) in patients younger than 3 months of age, was diagnosed earliest and RCC the latest (median age [months]: 0 and 154, respectively) both associated with significantly smaller TV (median TV [mL]: 67.2 and 45.0, respectively). RCC occurred in >14% of patients older than 120 months or older than 84 months with TV <100 mL. Receiver operating characteristic analyses discriminated WT from CMN, RCC and MRTK regarding age (AUC = 0.976, 0.929 and 0.791) and TV (AUC = 0.768, 0.813 and 0.622). MRTK had the highest risk of metastasis (37.9%) despite young age, whereas the risk of metastasis increased significantly with age in WT. Age and TV at diagnosis can differentiate WT from CMN and RCC. MRTK must be considered for metastatic tumours at young age. Identification of CCSK without histology remains challenging. Combined with MRI-characteristics, including diffusion-weighted imaging, and radiomics and liquid biopsies in the future, our approach allows optimization of biopsy recommendations and prevention of misdiagnosis-based neoadjuvant treatment.